E‐cadherin can limit the transforming properties of activating β‐catenin mutations. (3rd August 2015) - Huels, David J; Ridgway, Rachel A; Radulescu, Sorina; Leushacke, Marc; Campbell, Andrew D; Biswas, Sujata; Leedham, Simon; Serra, Stefano; Chetty, Runjan; Moreaux, Guenievre; Parry, Lee; Matthews, James; et al.
Abstract Wnt pathway deregulation is a common characteristic of many cancers. Only colorectal cancer predominantly harbours mutations in APC, whereas other cancer types (hepatocellular carcinoma, solid pseudopapillary tumours of the pancreas) have activating mutations in β‐catenin (CTNNB1). We have compared the dynamics and the potency of β‐catenin mutations in vivo. Within the murine small intestine (SI), an activating mutation of β‐catenin took much longer to achieve Wnt deregulation and acquire a crypt‐progenitor cell (CPC) phenotype than Apc or Gsk3 loss. Within the colon, a single activating mutation of β‐catenin was unable to drive Wnt deregulation or induce the CPC phenotype. This ability of β‐catenin mutation to differentially transform the SI versus the colon correlated with higher expression of E‐cadherin and a higher number of E‐cadherin:β‐catenin complexes at the membrane. Reduction in E‐cadherin synergised with an activating mutation of β‐catenin resulting in a rapid CPC phenotype within the SI and colon. Thus, there is a threshold of β‐catenin that is required to drive transformation, and E‐cadherin can act as a buffer to sequester mutated β‐catenin.